1993
DOI: 10.1073/pnas.90.10.4426
|View full text |Cite
|
Sign up to set email alerts
|

Association of casein kinase 2 with nuclear chromatin in relation to androgenic regulation of rat prostate.

Abstract: Casein kinase 2 (CK-2) is a ubiquitous messenger-independent protein serine/threonine kinase that has been implicated in growth control. We have studied the activity and subcelular location of CK-2 in adult rat ventral prostate in relation to androgen withdrawal and administration. Androgen deprivation by castration results in a faster decline in CK-2 activity associated with prostatic nuclei than that in the cytosol. Nuclear CK-2 associated with chromatin is reduced at an even greater rate than that in the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 30 publications
(35 reference statements)
3
39
0
Order By: Relevance
“…a These authors made equal contribution. b Present address: Northwestern Health Sciences University, Bloomington, MN both the nuclear and cytoplasmic compartments in the cell, and undergoes dynamic shuttling between various compartments which may relate to its functional activity in those compartments (Ahmed et al, 1993;Ahmed, 1994a, 1994b;Tawfic et al, 1996Tawfic et al, , 1997Guo et al, 1998Guo et al, , 1999aGuo et al, , 1999bAhmed et al, 2000;Faust and Montenarh, 2000). A key feature of CK2 cell biology is that it is essential for cell survival (e.g., Padmanabha et al, 1990), and accordingly, attempts to produce CK2-knockout mice have been unsuccessful (Bouchou et al, 2003).…”
Section: General Characteristics Of Protein Kinase Ck2mentioning
confidence: 99%
See 2 more Smart Citations
“…a These authors made equal contribution. b Present address: Northwestern Health Sciences University, Bloomington, MN both the nuclear and cytoplasmic compartments in the cell, and undergoes dynamic shuttling between various compartments which may relate to its functional activity in those compartments (Ahmed et al, 1993;Ahmed, 1994a, 1994b;Tawfic et al, 1996Tawfic et al, , 1997Guo et al, 1998Guo et al, , 1999aGuo et al, , 1999bAhmed et al, 2000;Faust and Montenarh, 2000). A key feature of CK2 cell biology is that it is essential for cell survival (e.g., Padmanabha et al, 1990), and accordingly, attempts to produce CK2-knockout mice have been unsuccessful (Bouchou et al, 2003).…”
Section: General Characteristics Of Protein Kinase Ck2mentioning
confidence: 99%
“…Regulation of cellular CK2 appears to be complex and various hypotheses have been proposed on this subject (for reviews, see e.g., Allende and Allende, 1995;Ahmed, 1999;Montenarh and Faust, 2000;Pinna, 2002;Filhol et al, 2004;Olsten et al, 2005). To explain some of our data on CK2 responses to altered cell growth, we originally proposed that CK2 undergoes dynamic shuttling between cytoplasm and nucleus and further within the nucleus it undergoes differential distribution depending on the conditions to which the cell is exposed (Ahmed et al, 1993;Ahmed, 1999;Ahmed, 1994a, 1994b;Tawfic et al, 1996Tawfic et al, , 1997Guo et al, 1998Guo et al, , 1999aGuo et al, , 1999bAhmed et al, 2000). Subsequently, it was demonstrated that CK2 translocation can take place to other parts of the cell further reinforcing the notion that dynamic intracellular shuttling of CK2 might represent a key mode of its regulation in the cell in response to diverse signals (Tawfic et al, 1997;Faust and Montenarh, 2000).…”
Section: General Characteristics Of Protein Kinase Ck2mentioning
confidence: 99%
See 1 more Smart Citation
“…FCS analysis also provides evidence for the existence of a subpopulation of slowmoving CK2 subunits that could represent integral components of less mobile structures, such as nuclear matrix or chromosome scaffold. Interestingly, a rapid translocation of CK2 to nuclear matrix associated with genomic activation upon induction of cell growth has been described in an in vivo physiological model (2,19). It could be also imagined that the previously described reversible polymerization of CK2 subunits (41) might also create transient, less-mobile nuclear complexes.…”
Section: Vol 23 2003 Dynamics Of Ck2 Subunits In Living Cells 983mentioning
confidence: 99%
“…The association of CK2 in these compartments is profoundly responsive to the status of growth stimuli (1,9,(11)(12)(13). To that end, we have employed androgen action in the prostate epithelial cells that is mediated via the androgen-receptor system as an experimental model.…”
mentioning
confidence: 99%